2022
DOI: 10.1038/s42003-022-03153-x
|View full text |Cite
|
Sign up to set email alerts
|

A pictorial account of the human embryonic heart between 3.5 and 8 weeks of development

Abstract: Heart development is topographically complex and requires visualization to understand its progression. No comprehensive 3-dimensional primer of human cardiac development is currently available. We prepared detailed reconstructions of 12 hearts between 3.5 and 8 weeks post fertilization, using Amira® 3D-reconstruction and Cinema4D®-remodeling software. The models were visualized as calibrated interactive 3D-PDFs. We describe the developmental appearance and subsequent remodeling of 70 different structures incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 196 publications
(293 reference statements)
1
48
0
Order By: Relevance
“…For a number of these stages, however, only one specimen was available for analysis ( Table 1 ). Due to the limited availability of intact human embryos for research, some published studies do rely on using one embryo per stage, making the assumption that these are representative of normal ( Hikspoors et al, 2022 ) or make comparisons to other databases ( Rana et al, 2014 ). The human embryos used in our study were all genotyped and found to be karyotypically normal, and with the expected morphology when compared to published studies of human developmental anatomy ( Congdon, 1922 ; Rana et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…For a number of these stages, however, only one specimen was available for analysis ( Table 1 ). Due to the limited availability of intact human embryos for research, some published studies do rely on using one embryo per stage, making the assumption that these are representative of normal ( Hikspoors et al, 2022 ) or make comparisons to other databases ( Rana et al, 2014 ). The human embryos used in our study were all genotyped and found to be karyotypically normal, and with the expected morphology when compared to published studies of human developmental anatomy ( Congdon, 1922 ; Rana et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of this anomaly suggests the coexistence of a variety of congenital cardiac defects, especially aortic arch anomalies and outflow tract malformations. While it is well established that the distal outflow tract separates into the intrapericardial trunks and the right and left pulmonary arteries develop extrapericardially, it is possible that the undue rotation of the aortopulmonary septum can produce crossing of the pulmonary arteries 11 …”
Section: Discussionmentioning
confidence: 99%
“…Our approach to creating this model was guided by two observations: (i) the HLHS heart in utero displays an intact ventricular septum, normally aligned great vessels, and concordant atrioventricular connections; and (ii) that this contrasts with the chick embryo model, in which left atrial ligation is performed during cardiogenesis and structural abnormalities other than left heart hypoplasia, such as ventricular septal defects, can occur (in approximately a quarter of surgically manipulated embryos) [ 18 , 32 ]. Therefore, we hypothesized that the insult leading to left heart growth failure likely occurs in the fetal period after the early cardiac developmental events have occurred (i.e., after looping, convergence, wedging, and septation events have taken place by weeks 8–9 of gestation [ 33 , 34 ]).…”
Section: The Flow Theory Of Hypoplastic Left Heart Syndromementioning
confidence: 99%
“…In the clinical setting, HLHS has been detected as early as 12 weeks of gestation with ultrasound [ 36 ]. This is still 3–4 weeks after the completion of cardiogenesis [ 33 , 34 ] during a period when the heart is growing rapidly. The left atrium embolization model demonstrates that HLHS can occur after cardiogenesis, but does not exclude it from occurring or being initiated earlier.…”
Section: The Flow Theory Of Hypoplastic Left Heart Syndromementioning
confidence: 99%